2016
DOI: 10.1038/srep25729
|View full text |Cite
|
Sign up to set email alerts
|

The cis-acting replication element of the Hepatitis C virus genome recruits host factors that influence viral replication and translation

Abstract: The cis-acting replication element (CRE) of the hepatitis C virus (HCV) RNA genome is a region of conserved sequence and structure at the 3′ end of the open reading frame. It participates in a complex and dynamic RNA-RNA interaction network involving, among others, essential functional domains of the 3′ untranslated region and the internal ribosome entry site located at the 5′ terminus of the viral genome. A proper balance between all these contacts is critical for the control of viral replication and translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 62 publications
1
38
0
Order By: Relevance
“…We hypothesize that the non-overlapping YTHDF binding sites in HCV RNA represent m 6 A sites not detected by MeRIP-seq due to biological variation, technical noise, or potentially sites that might be bound by YTHDF proteins in an m 6 A-independent fashion. Indeed, a recent report found that YTHDF proteins bound to an in vitro transcribed, hence non-methylated, HCV RNA genome (Rios-Marco et al, 2016). Therefore, future studies could very well reveal functions of the YTHDF proteins that are independent of m 6 A during the HCV life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the non-overlapping YTHDF binding sites in HCV RNA represent m 6 A sites not detected by MeRIP-seq due to biological variation, technical noise, or potentially sites that might be bound by YTHDF proteins in an m 6 A-independent fashion. Indeed, a recent report found that YTHDF proteins bound to an in vitro transcribed, hence non-methylated, HCV RNA genome (Rios-Marco et al, 2016). Therefore, future studies could very well reveal functions of the YTHDF proteins that are independent of m 6 A during the HCV life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, miR-200 regulates neuronal differentiation in the developing olfactory bulb, an effect that is mediated by inhibition of the zinc finger protein Zeb2 (Beclin et al, 2016). Previous research has shown that miR-200c expression is increased in the adult rodent spinal cord following injury (Yu et al, 2014), in the adult cerebral cortex following ischemic preconditioning (Lee et al, 2010), and following cerebrovascular stroke (Stary et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This process involves uncoating or at least relaxation of the viral RNP. Host factors likely interact with the viral RNP to maintain proximity of necessary factors and aid complex formation to initiate and complete these processes (67)(68)(69). It is likely that many of these interactions are weak and transient, acting as scaffolds for virus-driven processes.…”
Section: Discussionmentioning
confidence: 99%